Compromising with Ethiopianness after 1991: The Ethiopian Festival of the Millennium (September 2007-September 2008) - (:unkn) unknown (My University, 2013)
This article argues that imperial marks and symbols were central to the nation-building strategy of the leaders of the Ethiopian People's Revolutionary Democratic Front (EPRDF) before the outbreak of the 1998-2000 war against Eritrea and even before 1991. It thus presents the Ethio-Eritrean war, often perceived as a radical turning point concerning EPRDF's nation-building policy, in a different light. The study also highlights how two often opposed conceptions of the Ethiopian nation-i.e., Pan-Ethiopian and "multinational" 1-have actually been presented as compatible by EPRDF leaders in the last decades. It argues that these two conceptions do not appear exclusive of each other, and their equilibrium is more clearly manifested since the National Festival of the Millennium, celebrated from September 2007 to September 2008 to mark Ethiopia's entry into the third Millennium. The official narrations of Ethiopian statehood and nationhood expressed at this occasion confirmed the consistency of the new leaders' interpretation of what Ethiopia "was" and "shall be," but simultaneously show how current and concrete contingencies-here the post-1998-2000 war context and the turmoil of the 2005 general elections-force these same state/nation-builders to adjust their discourses.
Keywords: African Research